The Angiotensin II Type 1 Receptor-Associated Protein Attenuates Angiotensin II-Mediated Inhibition of the Renal Outer Medullary Potassium Channel in Collecting Duct Cells - Polidoro, Juliano Zequini; Rebouças, Nancy Amaral; Girardi, Adriana Castello Costa (Frontiers in Physiology, 2021)
Adjustments in renal K+ excretion constitute a central mechanism for K+ homeostasis. The ROMK channel accounts for the major K+ secretory route in collecting ducts during basal conditions. Activation of the angiotensin II (Ang II) type 1 receptor (AT1R) by Ang II is known to inhibit ROMK activity under the setting of K+ dietary restriction, underscoring the role of the AT1R in K+ conservation. The present study aimed to investigate whether an AT1R binding partner, the AT1R-associated protein (ATRAP), impacts Ang II-mediated ROMK regulation in collecting duct cells and if so, to gain insight into the potential underlying mechanisms. To this end, we overexpressed either ATRAP or β-galactosidase [LacZ]), used as a control, in M-1 cells, a model line of cortical collecting duct cells. We then assessed ROMK channel activity by employing a novel fluorescence-based microplate assay. Experiments were performed in the presence of 10-10 M Ang II or vehicle for 40 minutes. We observed that Ang II-induced a significant inhibition of ROMK in LacZ, but not in ATRAP-overexpressed M-1 cells. Inhibition of ROMK-mediated K+ secretion by Ang II was accompanied by lower ROMK cell surface expression. Conversely, Ang II did not affect the ROMK-cell surface abundance in M-1 cells transfected with ATRAP. Additionally, diminished response to Ang II in M-1 cells overexpressing ATRAP was accompanied by decreased c-Src phosphorylation at the tyrosine 416. Unexpectedly, reduced phospho-c-Src levels were also found in M-1 cells, overexpressing ATRAP treated with vehicle, suggesting that ATRAP can also downregulate this kinase independently of Ang II-AT1R activation. Collectively, our data support that ATRAP attenuates inhibition of ROMK by Ang II in collecting duct cells, presumably by reducing c-Src activation and blocking ROMK internalization. The potential role of ATRAP in K+ homeostasis and/or disorders awaits further investigation.